2021
DOI: 10.3389/feduc.2021.750281
|View full text |Cite
|
Sign up to set email alerts
|

What are we Really Aiming for? Identifying Concrete Student Behavior in Co-Regulatory Formative Assessment Processes in the Classroom

Abstract: Formative assessment has the potential to incite co-regulatory activities that foster student’s development of self-regulatory skills. Teacher often intend to use formative assessment to foster self-regulation. However, this requires purposeful interaction between students and teachers. To improve co-regulatory formative assessment implementation, research and professional development needs to pay attention to what co-regulatory formative assessment look like. This participatory study explores if and how the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 35 publications
0
11
0
2
Order By: Relevance
“…It may indeed be possible that just the structure that AfL provides, such as clear expectations, frequent assessments, and feedback, helped to develop students' metacognitive skills (Nicol & MacFarlane-Dick, 2006). Our findings could also demonstrate the proposed overlap between activities related to AfL and metacognition, such as working towards specific goals and monitoring the progress towards these goals (Gulikers et al, 2021;Panadero et al, 2018).…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…It may indeed be possible that just the structure that AfL provides, such as clear expectations, frequent assessments, and feedback, helped to develop students' metacognitive skills (Nicol & MacFarlane-Dick, 2006). Our findings could also demonstrate the proposed overlap between activities related to AfL and metacognition, such as working towards specific goals and monitoring the progress towards these goals (Gulikers et al, 2021;Panadero et al, 2018).…”
Section: Discussionmentioning
confidence: 64%
“…The use of feedback may be the most complex strategy of all, as the effects of feedback on student achievement are inconsistent and not always positive (Brooks et al, 2021). Recent studies (Gulikers et al, 2021;Panadero et al, 2018) have suggested that student involvement in the other AfL(-related) strategies may be beneficial for students' feedback use. Students can be stimulated to improve their own learning process based on feedback only when that feedback gives information on where students are compared to the learning goals and success criteria.…”
Section: Assessment For Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…However, questions remain as to the number of data-points needed for meaningful intermediate decision-making, the timing of intermediate-decision-making, what kind of data-points and feedback are most helpful, and what enables students to take feedback on board and improve learning. The theoretical notion of feedback as a cyclic process involving dialogue and meaning-making as expressed in PA principle 4 (Carless et al, 2011;Boud and Molloy, 2013;Gulikers et al, 2021) needs to be further carved out in practical design choices. Here, recent research into feedback literacy of students and teachers (Boud and Dawson, 2021;Nicola-Richmond et al, 2021) might enhance the design choices made, and the implementation of PA in practice.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…PA seeks to gradually increase students' agency for their own learning process and progress, starting from rather structured and curriculum/teacher-controlled assessment to self-owned assessment and learning (Schut et al, 2018;Torre et al, 2020). Also, feedback is most effective when it is a loop, a cyclic process involving dialogue (Carless et al, 2011;Boud and Molloy, 2013;Gulikers et al, 2021). Recurrent meetings with mentors/coaches need to support self-analysis of all assessment data (Heeneman and de Grave, 2017) and students' feedback literacy needs to be supported and gradually developed (Price et al, 2011;Schut et al, 2018).…”
Section: Programmatic Assessment Principlementioning
confidence: 99%